Interaction Between Construction Land Expansion and Cropland Expansion and Its Socioeconomic Determinants: Evidence From Urban Agglomeration in the Middle Reaches of the Yangtze River, China - Wang, Liye; Zhang, Siyu; Liu, Yanfang; Liu, Yaolin (Frontiers in Environmental Science, 2022)
Both urbanization and cropland expansion are hot issues recently. However, researches related to the spatiotemporal interaction between urbanization and cropland expansion and their socioeconomic determinants remain scarce. Accordingly, this research takes the urban agglomeration in the middle reaches of the Yangtze River (MRUA) as the research area by combining spatial analysis, sensitivity analysis, and the spatial gravity model. To achieve this goal, we identified the area of the construction land expansion and cropland expansion, the sensitivity of cropland expansion to construction land expansion, the shifting trajectory of gravity centers of construction land expansion and cropland expansion and their interaction during 2000-2020, respectively. Additionally, the geographically weighted regression model was utilized to explore the spatiotemporal heterogeneity of four socioeconomic determinants of the interaction between construction land expansion and cropland expansion. The results are as follows: (1) the area of the expanded construction land and the expanded cropland and the sensitivity of cropland expansion to construction land expansion show an overall increasing pattern; (2) the gravity center of the expanded construction land shifted toward the northeast, whereas that of the expanded cropland moved to the southeast but with similar moving distances (17.83 and 15.37 km, respectively); (3) the GDP has an increasing positive effect on the interaction of the construction land expansion and cropland expansion, whereas the investment in fixed assets shows an increasing negative effect during 2000-2020. The GDP in the agricultural sector and population displays a stable influence. This paper offers a solution for decision makers to promote the interaction between construction land and cropland.